THE EFFECT OF NEURO-ENTREPRENEURSHIP, DECISION-MAKING HEURISTICS, SOCIAL MEDIA VIRALITY, AND COMMUNITY-BASED MARKETING ON FOOD PRODUCT BRAND EQUITY - Rahman, Kristanti; Wulandjani, Harimurti; Zulfikri, Agung (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study investigates the effect of neuro-entrepreneurship, decision-making heuristics, social media virality, and community-based marketing on the brand equity of food products. Employing a quantitative approach with 350 respondents, the study uses structural equation modeling (SEM) to analyze the relationships among variables. The results reveal that all four factors significantly and positively influence brand equity, with community-based marketing having the strongest impact. The findings emphasize the importance of integrating cognitive, behavioral, digital, and social strategies to build strong food brands. This research contributes to both academic theory and practical marketing by providing a multidimensional understanding of brand equity formation in the evolving food market. Recommendations for entrepreneurs include leveraging neurological insights, simplifying consumer decision processes, harnessing social media virality, and fostering community engagement.